In-vivo assesment of the genotoxic and oxidative stress effects of particulate matter on Echinogammarus veneris. (April 2017) - Marcoccia, Melissa; Ronci, Lucilla; De Matthaeis, Elvira; Setini, Andrea; Perrino, Cinzia; Canepari, Silvia
Abstract: Seven types of atmospheric dusts (road dust, soil dust, brake dust, desert dust, pellet ash and coke and certified material NIST1648a – urban dust) have been tested for their genotoxicity on specimens of Echinogammarus veneris, a small aquatic amphipod. Experiments were carried out in vivo, by exposing the animals for 24 h to water containing 25 mg/L of dust. Each dust has been chemically analyzed for ions, elemental carbon, organic carbon and for the soluble and insoluble fractions of elements. Non-specific damages to DNA have been evaluated by the comet test, while oxidative damages have been estimated by coupling the comet test with formamido pyrimidine DNA glycosylase reaction. The animal tissues have been acid digested and analyzed for their elemental content to evaluate the bioaccumulation. All the considered dusts have caused a significant non-specific DNA damage, while the oxidative stress was shown only by dust types containing high concentration of elements. Furthermore, the oxidative damage has shown a positive correlation with the total bio-accumulated elemental concentration. For all the dust samples, the correlation with bio-accumulation in the tissues was more satisfactory for the insoluble fraction than for the soluble fraction of elements. Elements contained in solid particles seem then to be the main responsible bioaccumulation and for the oxidative stress. Highlights: E . veneris is a suitable bio-indicator of DNA damages caused by atmospheric dusts. Non-specific and oxidative DNA damages were evaluated on haemocyte cells. The insoluble fraction of elements is bio-accumulated in the gammarid tissue. Oxidative stress is mainly related with the insoluble fraction of elements in PM.